Constitutional originalism : a debate - Bennett, Robert W. (Robert William), 1941-; Solum, Lawrence (Ithaca : Cornell University Press, 2016)
Constitutional originalism is the theory that fidelity to the original understanding of the US Constitution should constrain contemporary judges. The current book looks at the arguments for and against this originalism.
Previously issued in print: 2011.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 9, 2016).
Keywords: Constitutional law -- United States; Law; Constitution: government & the state; Methods, theory & philosophy of law; Laws of specific jurisdictions & specific areas of law; Constitutional & administrative law: general